1973
DOI: 10.1111/j.1365-2222.1973.tb01331.x
|View full text |Cite
|
Sign up to set email alerts
|

The radioallergosorbent test with a purified allergen from codfish

Abstract: Summary The radioallergosorbent test (RAST) was performed with a purified allergen (DS 22) from cod, coupled to CNBr‐activated cellulose discs. A 100% correlation was found between a positive RAST and the presence of clinical allergy to cod in fifty‐six children as compared to a negative RAST in all sera from fifty‐six allergic children tolerating fish. Positive results were obtained with discs treated with DS 22 in a concentration as low as 0.4 ng/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
1

Year Published

1976
1976
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(37 citation statements)
references
References 26 publications
(8 reference statements)
5
31
0
1
Order By: Relevance
“…Other studies have clearly shown that purified allergens increase the precision of RAST [2,3,15] and the varying precision of RAST has highlighted the unsatisfactory quality of many allergen extracts. It is obvious that if an extract contains a high amount of nonallergenic components with an affinity for the activated sites similar to or higher than the allergen components then this will result in a low allergen representation on the test particles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have clearly shown that purified allergens increase the precision of RAST [2,3,15] and the varying precision of RAST has highlighted the unsatisfactory quality of many allergen extracts. It is obvious that if an extract contains a high amount of nonallergenic components with an affinity for the activated sites similar to or higher than the allergen components then this will result in a low allergen representation on the test particles.…”
Section: Discussionmentioning
confidence: 99%
“…Various degrees of relationship have been noted between in vivo and in vitro determinations, to some extent depending on the types of allergens used. Thus, a 100% correlation has been found with the purified and well-character ized cod allergen [3,15] while only 59% agreement was found utilizing house dust extract as allergen [2], Three studies with several allergens on randomly selected ma terial from children have revealed agree ments between RAST and PT of 84%> [6] and 77% [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a food has been avoided for a long period and antigenic stimulation has been lacking, the level of specific IgE in the serum by RAST may be low or undetectable; after ingestion of the food the serum level and RAST value may increase considerably fi-om a booster effect of antigen in a sensitized person (54). These may be explanations for the finding that the skin test seems to be superior to RAST for detection of reaginic sensitization to food antigens and identification of persons who will develop symptoms in food challenges (64)(65)(66)(67).…”
Section: Radioallergosorbent Test (Rast)mentioning
confidence: 99%
“…Many of them possess similar physicochemical properties (e.g., ac idity) [1,4], Whole pollen extracts are characterized by a heterogeneity in their protein content, many of which are not allergenic. This is true for ragweed as well as for grass pollen [9,10,12,14].…”
Section: Discussionmentioning
confidence: 99%